A novel strategy for constructing a highly conductive and swelling-resistant semi-flexible aromatic polymer based anion exchange membranes. (13th April 2017) - Zhao, Baolin; He, Gaohong; El Hamouti, Issam; Gao, Li; Liu, Yanjun; Deng, Runlian; Yan, Xiaoming
Abstract: A novel strategy was proposed to construct a bicontinuous hydrophilic/hydrophobic micro-phase separation structure which is crucial for high hydroxide conductivity and good dimensional stability anion exchange membranes (AEMs). A semi-flexible poly (aryl ether sulfone) containing a flexible aliphatic chain in the polymer backbone with imidazolium cationic group was synthesized by the polycondensation of bis(4-fluorophenyl) sulfone and the self-synthesized 4, 4′-[butane-1, 4-diylbis(oxy)] diphenol followed by a two-step functionalization. The corresponding membranes were prepared by solution casting. More continuous hydroxide conducting channels were formed in the semi-flexible polymer membranes compared with the rigid based ones as demonstrated by TEM. As a result, given the same swelling ratio, hydroxide conductivity of the semi-flexible polymer membrane was about 2-fold higher than the one of the rigid polymer based membrane (e.g., 45 vs. 22 mS cm −1 with the same swelling ratio of 24% at 20 °C). The highest achieved conductivity for the semi-flexible polymer membranes at 60 °C was 93 mS cm −1, which was much higher those of other random poly (aryl ether sulfone) based imidazolium AEMs (27–81 mS cm −1 ). The single cell employing the semi-flexible polymer membrane exhibited a maximum power density of 125 mW cm −2 which was also higher than those for other random poly (aryl ether sulfone) based imidazolium AEMs (16–105.2 mW cm −2 ). Highlights: A novel semi-flexible polymer membrane was prepared. The Semi-f-PAES-ImOH membrane exhibited high hydroxide conductivity. The Semi-f-PAES-ImOH membrane showed good dimensional stability.